Morphological and molecular characterization of anamorph associated with gray mold of castor (Ricinus communis L.): CHARACTERIZATION OF ANAMORPH ASSOCIATED WITH CASTOR GRAY MOLD - C YAMUNA; P KISHORE VARMA; R D PRASAD; K VIJAYA LAKSHMI (Journal of Oilseeds Research, 2015)
Graymold of castor caused by the anamorph ofBotryotinia ricini isthe most important disease and causessevere losses when there are heavy and continuous rains during capsule formation stage. In the present investigation, the anamorph of B. ricini was characterized based on morphological and molecular studies. The size of conidia and conidiophores were recorded from the culture grown on oat meal enriched medium for morphological characterization. Cultural characters like colony colour, growth pattern and sclerotial production were studied on six growth media.Based on microscopic observations, the anamorph wasidentified as Amphobotrysricini. Further, the identity was confirmed by amplifying fungal DNA using two universal Internal Transcribed Spacer (ITS) primers, ITS1 and ITS4 in a polymerase chain reaction. A single 0.5 kb band was amplified and amplified region is sequenced and analyzed in a standard Gen Bank BLAST search for fungal species identification. BLAST search has shown 99% similarity of the query sequence with Amphobotrys ricini. The results of this study confirmed that A. ricini is the anamorphic state associated with castor gray mold in Hyderabad region of Telangana state.